(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The development and introduction of new crop varieties are crucial for ensuring high agricultural productivity. This article explores the importance of breeding new crop varieties to enhance yield, resistance to diseases, and adaptability to changing climatic conditions. By examining recent advancements in agricultural biotechnology and plant breeding, this study highlights the role of new varieties in achieving sustainable agricultural practices and meeting the growing global food demand. The paper also discusses the challenges and opportunities in the development of high-yielding crop varieties, emphasizing the need for continuous research and innovation in this field.